1996
DOI: 10.1111/j.1346-8138.1996.tb04013.x
|View full text |Cite
|
Sign up to set email alerts
|

Urticarial Vasculitis with Papular Lesions in a Patient with Type C Hepatitis and Cryoglobulinemia

Abstract: We describe a case of urticarial vasculitis accompanied by erythematous wheals, palpable pupura, and subsequent necrotic ulcerated papular lesions in a patient with type C chronic hepatitis and type II cryoglobulinemia (IgM-kappa and polyclonal IgG). A 56-year-old man developed recurrent urticarial lesions on his lower extremities and trunk. The histology revealed leukocytoclastic vasculitis with perivascular immunoglobulin deposits. Subsequently, multiple reddish papular lesions with necrotic ulcerations appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…auch hämorrhagische Blasen und Beinulzera [25,38,50]. Beschrieben wurde ferner das Auftreten von Urtikaria-Vaskulitis [36,39] und Pyoderma gangraenosum [56] bei HCV-assoziierter Kryoglobulinämie.…”
Section: Weitere Mit Hcv-infektion Assoziierte Dermatosenunclassified
“…auch hämorrhagische Blasen und Beinulzera [25,38,50]. Beschrieben wurde ferner das Auftreten von Urtikaria-Vaskulitis [36,39] und Pyoderma gangraenosum [56] bei HCV-assoziierter Kryoglobulinämie.…”
Section: Weitere Mit Hcv-infektion Assoziierte Dermatosenunclassified
“…This study by Kanazawa et al 12 is the only published work suggesting a possible link between HCV and chronic urticaria, whereas all other studies, including the present one, showed nonsignificant results. Few patients in the world literature have both urticaria and HCV infection (Table 2), 7,[11][12][13][14][15][29][30][31] except those with mixed cryoglobulinemia, who have urticarial vasculitis rather than true urticaria. On the other hand, in a previous study 8 of a systematic cutaneous examination of 100 HCV-infected patients, none of the patients had present or past urticaria.…”
Section: Commentmentioning
confidence: 99%
“…Single case reports include colon carcinoma (42), polycythemia vera (43), Muckle–Wells syndrome (44), and Cogan's syndrome (45). Urticarial venulitis has been noted in patients with hepatitis B (46,47) and C (30,48) virus infections, infectious mononucleosis (49), Lyme borreliosis (50), and in the shunt nephritis syndrome with bacteremia, mixed cryoglobulinemia, and glomerulonephritis (51). The relation of urticarial venulitis to other conditions in these anecdotal reports needs to be confirmed.…”
Section: Associated Conditionsmentioning
confidence: 99%